Dinamika Toleransi Jamaat Ahmadiyah Indonesia (JAI) di Jawa Barat - Susanti, Reni; Kurniawan, Rio; Rantona, Safutra; Meltareza, Ridma; Sirait, Rinda A (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2025)
The existence of minority groups often leads to conflict in a homogeneous community. Differences, misdirection, are often blamed on those who are considered controversial. One of the minority groups of public concern is the Jemaat Ahmadiyah Indonesia (JAI) in Tenjowaringin Village, Salawu District, Tasikmalaya Regency, West Java Province. In 2005 and 2013 there were conflicts between JAI and non-JAI groups in Tenjowaringin. The conflict caused damage to buildings, closure of houses of worship, and hampered communication interactions between the two groups. This study uses a qualitative interview and observation techniques. There were 8 informants among JAI and non-JAI groups. The informants represented residents, community leaders, and the local village government. The research observations were carried out for two months in Tenjowarigin Village, Salawu District, Tasikmalaya Regency. The results of the study explained that the conflict caused distrust between groups, including the closing of the mosque by non-JAI groups and making it difficult for JAI groups to carry out worship. To restore communication activities between the two groups, the two groups re-established post-conflict interaction through several activities initiated by the community or village government such as volleyball and eye donors. Keywords: The Dynamics of Communication, Conflict, Tolerance, Minority.